1997
DOI: 10.17578/1-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-Movements of European Equity Markets Before and After the 1987 Crash

Abstract: This article studies the changes in the co-movements of the twelve largest European equity markets after the 1987 international equity market crash. Tests based on Box M and principal component analysis indicate that the comovements of these equity markets changed significantly after the crash. Low correlations among national equity markets are often presented as evidence in support of the benefits of international portfolio diversification. The findings indicate that correlations among the twelve largest Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 24 publications
1
64
1
4
Order By: Relevance
“…Also, Kim et al (2005) examine the influence of the EMU on the dynamic process of stock market integration using a bi-variate EGARCH framework with time-varying conditional correlations. However, several studies, including Roll (1988), Hamao et al (1990), Lau and McInish (1993), Rahman and Yung (1994), and Meric and Meric (1997), document a significant increase in correlations and volatility transmission between equity markets during, and after, the 1987 international equity market crash. Recently, Kenourgios et al (2011) support the herding behavior after the 2008 US subprime crisis among five emerging Balkan markets.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Kim et al (2005) examine the influence of the EMU on the dynamic process of stock market integration using a bi-variate EGARCH framework with time-varying conditional correlations. However, several studies, including Roll (1988), Hamao et al (1990), Lau and McInish (1993), Rahman and Yung (1994), and Meric and Meric (1997), document a significant increase in correlations and volatility transmission between equity markets during, and after, the 1987 international equity market crash. Recently, Kenourgios et al (2011) support the herding behavior after the 2008 US subprime crisis among five emerging Balkan markets.…”
Section: Introductionmentioning
confidence: 99%
“…This topic has attracted considerable attention over the last few decades (see for example, Divecha, Drach & Stefek, 1992;DeFusco, McLeavey, Pinto & Runkle, 1996;Michaud, Bergstrom, Frashure & Wolahan, 1996;Meric & Meric, 1997). More recently Li et al (2003) showed that even though markets were becoming more integrated, this integration does not eliminate the benefit of diversifying into emerging markets.…”
Section: International Studiesmentioning
confidence: 99%
“…Previous studies showed that the worldwide financial markets become more integrated after the major turbulent economic event [19,20] . Furthermore, [21] suggest that contagion between markets occurs as a result of attempts by rational agents to infer information from price changes in other markets.…”
Section: Decomposition Of Stock Returnsmentioning
confidence: 99%